DESIGN AND PROPERTIES OF ASPHALT CONCRETE MODIFIED WITH CRUMB RUBBER AT HOT AND ARID REGION - A. M. Hmade1, Mohmed Alshekh; Setyawan, Ary; Purwana, Yusep Muslih (Jurnal Teknik Sipil, 2015)
AbstractMany researchers have been conducted in finding alternative materials in order to be used as a modifier in asphalt mixture for the purpose of improving its properties. This thesis presents a study of laboratory evaluation on the performance of hot-mixed asphalt (HMA) using crumb rubber as an additive. It is noted that crumb rubber was identified to have potency as a modifier in HMA due to the elastic behavior exposed by the rubber particles, especially in reducing the rutting potential. In this research, fine crumb rubber Shred (2.36-0.85 mm) obtained by ambient-temperature grinding process from discarded truck tires, was used to modify asphalt concert. The fine crumb rubber with different contents, i.e. 2.5%, 5%, 7.5% and 10%, was incorporated into the mixture by using dry process method. The Marshal properties, Unconfined Compressive Strength (UCS), Indirect Tensile Strength test (ITS) and Indirect Tensile Strength Modulus (ITSM), Permeability were conducted. The result showed that marshal stability, Marshal Quotient, Voids in Mix (VIM) and Voids in mineral aggregate (VMA) decreased with the increasing crumb rubber modifier. However, Marshal Flow and Void filled with asphalt (VFWA) increased when crumb rubber modifier was increased. All the values of unconfined compressive strength (UCS) y=-346.6x+5093at 30C?, Indirect Tensile Strength test (ITS) Y=-6.248x+404.9 with 0%CR, Y=-4.051x+254.8 with 2.5%CR, Y=-3.674x+223.5 with 5.0%and y=-2.820x+173.4 with 7.5%CRand Indirect Tensile Strength Modulus (ITSM) Y=-29000XÂ²-4259+682.7 at 40CÂ°, Permeability decreased with an increase in crumb rubber modifier. Therefore, Crumb rubber could not let commented as aggregate substitution for flexible asphalt concrete at hot and arid region.Keywords: Asphalt concrete Crumb Rubber modifier Marshall, ITS, ITSM, UCS, PermeabilityTest.